Penilaian pelaksanaan mata pelajaran vokasional - Landskap dan nurseri (MPV-LN) di peringkat sekolah menengah di semenanjung Malaysia / Gunasegaran a/l Raman - Raman, Gunasegaran (2014)

(untitled)
The purpose of this study was to evaluate the implementation of Vocational Subject-Landscape and Nursery (VS-LN) at secondary school level based Stufflebeam’s (1971) model of evaluation. A programme evaluation research design with quantitative and qualitative methodology was used. Research instruments consisting of questionnaires, observations and interviews were used. The participants in this study were 321 VS-LN students and 42 VS-LN teachers from secondary schools. Findings from the context domain show that, in general VS-LN courses fulfilled the needs of the VS-LN teachers but their uncertainties about some courses such as Landscape and Nursery business planning, management and maintenance of VS-LN tools and machines, give an impression that the courses are insufficient. While in input domain disclosed that the VS-LN equipments were suitable but VS-LN teachers and students were uncertain regarding the adequacy and the functioning of the VS-LN equipments. They were also found to be uncertain regarding the suitability, adequacy and the functioning of the VS-LN workshop amenities. Their uncertainties about the mentioned aspects imply that the stocks were not properly recorded and managed. Besides that, VS-LN teachers and students may not have enough knowledge about the VS-LN equipments and workshop amenities. The findings from the domain of process show that the safety precautions were generally implemented but research observations show that the safety precautions were not given importance during the practical session of VS-LN. Teaching and learning in the VS-LN programme in terms of teaching time distribution for theories and practical, teaching methods, competency assessment, and teacher-student interaction have been implemented according to the plan. The VS-LN students agreed that they were given opportunity to do activities according to their abilities and have knowledge about their responsibilities and rights in the implementation of competency assessment in the VS-LN programme. The VS-LN teachers agreed that the main obstacle in the implementation process of VS-LN was the VS-LN students who had difficulties in reading, writing and basic mathematics. Findings from the domain of product show that the former students of VS-LN programme admitted that the knowledge and skills acquired from VS-LN programme can be applied in their work and to further their studies but they are not confident to launch a business in the field of Landscape and Nursery as they feel they lack the required experience and knowledge. It is recommended that the VS-LN programme be continued with some improvements such as upgrading the VS-LN courses offered to the VS-LN teachers in order to implement the VS-LN programme effectively. External parties who are not supplying equipments and providing maintenance according to the contracts should be terminated. Students who are weak in reading, writing and basic mathematics should go through remedial classes. Besides that, VS-LN students should be exposed to business in the field of Landscape and Nursery through collaboration between school and companies involved in the related business.